Analisa Pengaruh Kinerja Mandor Terhadap Kualitas Proyek Konstruksi (Studi Kasus: Proyek Renovasi Villa Pasraman Bhagawan, Jimbaran, Kec. Kuta Selatan Kab. Badung) - Kariyana, I Made; Putra, I Komang Alit Astrawan; Ahdan, Alan; Pamungkas, Tri Hayatining; Diana, Anita Intan Nura (Fakultas Teknik, Universitas Wiraraja, 2025)
Construction developments in Bali have experienced great progress in recent years, especially in the construction of hotels, resorts and villas. This attracts the interest of many investors to invest in building villas in Bali. An important factor that determines project success is the planning of human resources who are directly involved in project work, especially foremen. One of the projects experiencing delays is the Pasraman Bhagawan Villa Renovation Project. This delay is caused by a focus on the quality of work so that it goes according to plan. Therefore, this study aims to analyze the influence of foreman performance on work quality and the factors that influence it. This research uses data collection methods by distributing questionnaires and multiple linear regression analysis. Based on the analysis results, the R-Square value obtained was 0.949, which means that the foreman's performance influenced 94.9% of the quality of the Pasraman Bhagawan Villa Renovation Project in Jimbaran. Management factors are the most dominant factors influencing project quality with a t count of 4.114. More efficient management of time, resources and budget will help avoid delays and ensure project quality is maintained.